Advanced Technique for Removal Of Salt & Pepper Noise In Images (International Journal of Engineering and Computer Science, 2018)
Transmission of images are overcome channels, Due to unwanted communication the salt and pepper noise is occur in images. The word salt and pepper noise is also speaks out a Impulse noise. The filtering mainly used for removal of impulse noise or salt and pepper noise for noise free images and fully recovered by minimum signal distortion also uncorrupted the images. For best solutions of removal of salt and pepper noise is a nonlinear digital filters which is based on order statistics of median filter. The Median filters are remove noisy signal and unwanted signals without damaging the corners .Median filter are operates in low densities but not in higher densities because at higher the image are blurred and damage the image. The filtering leaves the uncorrupted pixels and accepts the corrupted pixel. Median filter is applied to image unconditionally to practiced of conventional schemes for alert the intensities of remove the noisy signal from image then the results between the corrupted and uncorrupted pixels are prior to applying nonlinear filtering is highly desirable in images. The process of "Adaptive Median "filter is to identifies the noisy images or pixels and then remove the noisy pixels and replace them at same position by using the median filters or its variants, where the remaining are same or unchanged. The Adaptive median filter is best for removal of noisy pixels at low level. But at high level noise the adaptive median filter is provide a large Window size it is not to fit the pixel. The Adaptive median filter is also known as "switching" and "decision based" system. The existing system are Robust Estimation Algorithm (REA), Adaptive Median Filter (AMF), Standard Median Filter(SMF), it shows best performances at low noise level and at high noise level bad. A new Weighted Median Filter (WMF) is best for high noise level is an proposed.